Terrorism and counterterrorism today - Deflem, Mathieu (Sociology of crime, law, and deviance, 2015)
This volume contains chapters dealing with a variety of issues related to terrorism and counterterrorism and the study thereof, especially in relation to crime, criminal justice, law, and social control. The book gathers chapters involving a variety of issues and multiple theoretical approaches and methodological orientations. The topics include, amongst others, lone-wolf terrorism, the policing of terrorism, radicalization, suicide terrorism, torture, and counterterrorism policies. The themes of the book remain timely some 15 years after the events of September 11 2001 as evinced from the manifold continuing terrorism-related issues around the world today. This collection will be useful to students and scholars in sociology, criminology, law, political science, and public policy.